2013
DOI: 10.1002/ab.21478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxytocin on Women's Aggression Depend on State Anxiety

Abstract: (2013) 'E ects of oxytocin on women's aggression depend on state anxiety.', Aggressive behavior., 39 (4). pp. 316-322. Further information on publisher's website:https://doi.org/10.1002/ab.21478 Publisher's copyright statement: This is the accepted version of the following article: Campbell, A. and Hausmann, M. (2013), E ects of Oxytocin on Women's Aggression Depend on State Anxiety. Aggressive Behavior, 39 (4): 316-322, which has been published in nal form at https://doi.org/10.1002/ab.21478. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Furthermore, previous human studies have examined the acute effects of OT on experimentally induced aggression. Campbell and Hausmann (2013) found that OT moderated reactive aggression in women with highstate anxiety, but not in those with low-state anxiety. Alcorn et al (2015a) investigated the effect of an intranasal placebo, and 12, 24 and 48 IU of OT in six adult men with antisocial personality disorder and substance use disorder.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, previous human studies have examined the acute effects of OT on experimentally induced aggression. Campbell and Hausmann (2013) found that OT moderated reactive aggression in women with highstate anxiety, but not in those with low-state anxiety. Alcorn et al (2015a) investigated the effect of an intranasal placebo, and 12, 24 and 48 IU of OT in six adult men with antisocial personality disorder and substance use disorder.…”
Section: Introductionmentioning
confidence: 95%
“…However, recent literature suggests that individual and contextual differences may impact the effects of intranasal oxytocin on social stress reactivity (Bartels, 2012; Bertsch et al, 2012; Campbell and Hausmann, 2013; DeWall et al, 2014). For example, in a study of non-human primates, oxytocin increased social contact in subordinate males but not in dominant males (Winslow and Insel, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…SFBC in this case is in line with the research recommendations of Campbell et. al [8], that is, to manage aggressive behavior through the things behind it and then directing it to behave constructively is a very important thing done in the process of giving intervention.…”
Section: B Discussionmentioning
confidence: 99%